Chemosensory Learning in the Cortex - Rolls, Edmund (Frontiers in Systems Neuroscience, 2011)
Taste is a primary reinforcer. Olfactory-taste and visual-taste association learning takes place in the primate including human orbitofrontal cortex to build representations of flavour. Rapid reversal of this learning can occur using a rule-based learning system that can be reset when an expected taste or flavour reward is not obtained, that is by negative reward prediction error, to which a population of neurons in the orbitofrontal cortex responds. The representation in the orbitofrontal cortex but not the primary taste or olfactory cortex is of the reward value of the visual / olfactory / taste / input as shown by devaluation experiments in which food is fed to satiety, and by correlations with the activations with subjective pleasantness ratings in humans. Sensory-specific satiety for taste, olfactory, visual, and oral somatosensory inputs produced by feeding a particular food to satiety are implemented it is proposed by medium-term synaptic adaptation in the orbitofrontal cortex. Cognitive factors, including word-level descriptions, modulate the representation of the reward value of food in the orbitofrontal cortex, and this effect is learned it is proposed by associative modification of top-down synapses onto neurons activated by bottom-up taste and olfactory inputs when both are active in the orbitofrontal cortex. A similar associative synaptic learning process is proposed to be part of the mechanism for the top-down attentional control to the reward value vs the sensory properties such as intensity of taste and olfactory inputs in the orbitofrontal cortex, as part of a biased activation theory of selective attention.